Ảnh hưởng của nanoclay đến tính chất của vật liệu polyme compozit trên cơ sở nhựa epoxy DER 331 gia cường bằng sợi thủy tinh - Quyền, Nguyễn Công; Chương, Bùi; Yến Oanh, Đoàn Thị; Quyên, Nguyễn Khánh (Vietnam Journal of Chemistry, 2015)
Polymer composite materials based on epoxy-nanoclay matrix and glass fiber reinforcement have been studied. The results show the addition of 2phr nanoclay I28E into epoxy DER331 system can improve wetting ability of matrix onto glass, that lead to enhanced adhesion between epoxy matrix and glass fiber reinforcement. As a consequence, the energy for layers separation GIC and fatigue resistance of composites with epoxy-nanoclay matrix are considerable higher (1.5 and 1.7 times accordingly) than that of with neat epoxy matrix.